Praktik Politik Identitas dalam Akun Media Sosial Anies-Sandi - Triantoro, Dony Arung (FISIP Universitas Atma Jaya Yogyakarta, 2019)
Abstract: The DKI Jakarta Election Contest 2017 is inseparable from the discourse of politicization of ethnic, religious, racial, and intergroup issues (SARA) in campaign activities. This study aims to examine the practice of identity politics carried out by Anies-Sandi in their social media account. The results of this study indicate that the practice of identity politics in their social media account tends to display Islamic religious symbols. The strengthening practice of this identity politics represents the emergence of radical Islamic movements, conservatives, Islamism, and upper-middleclass muslims in Indonesia. Finally, identity politics will slowly weaken Pancasila democracy in Indonesia.Keywords: blasphemy, identity politics, social media